Tensile behavior of plastic fiber reinforced concrete - Tjong, Andi Sanjaya. (2010)
Concrete is a construction material, mainly composed from cement, water, and aggregates. Concrete has a relatively high compressive strength but low tensile strength, which causes cracking problems. As a brittle material, plain concrete fails suddenly once the deformation corresponding to the ultimate tensile strength is exceeded; therefore to solve this problem, fiber reinforced concrete (FRC) is introduced. Fiber reinforced concrete contains relatively short, discontinuous discrete fibers and it is used to increase the tensile strength and ductility of the concrete specimen. The purpose of this project is to analyze the tensile behavior of plastic fiber (Polypropylene) reinforced concrete. Several combinations of lengths and fiber contents were selected to investigate their influences in the concrete specimen. Finally, it can be concluded that the presence of plastic (Polypropylene) fibers in fiber reinforced concrete improves the tensile strength and ductility of the concrete.